The use of dysphemism in the Japanese film: Kizudarake no Akuma - Nisfalaila, Alya; Hamidah, Idah; Firmansyah, Dian Bayu (Japanese Research on Linguistics, Literature, and Culture, 2022)
The study examined the use of dysphemism in a Kizudarake no Akuma film which aimed to describe the forms and functions of dysphemism in the movie Kizudarake no Akuma. This research is a qualitative descriptive study with data analysis method using the extralingual equivalent method. Data validation is done with native speakers. The data source is a film entitled Kizudarake no Akuma. Research data collection is conducted by note-taking technique. The data were identified and analyzed based on the dysphemism theory from Allan and Burridge (2017), the context theory from Saifudin (2018) and the speech component theory from Hymes (2017). The results of this study found 7 types of dysphemism that appeared in the data source, including: 1) the form of taboo terms, 2) cursing and obscenity, 3) comparisons of humans with animal traits, 4) dysphemism nicknames from physical characters, 5) cuss from mental abnormality, 6) derision with a tone of contempt, and 7) terms from a foreign language. Based on the results of the study, it can be concluded that the most widely found type of dysphemism is type 1 with a total of 6 data, consisting of 4 data in oral form with the functions: a) showing anger, b) expressing frustration, and c) as insulting or ridicule; and 2 data in written form with the following functions: a) as an insult or ridicule and b) an expression of dislike.  Penelitian ini mengkaji mengenai penggunaan disfemisme dalam film Kizudarake no Akuma yang bertujuan untuk mendeskripsikan bentuk-bentuk serta fungsi dari disfemisme yang terdapat dalam film Kizudarake no Akuma. Penelitian ini merupakan penelitian deskriptif kualitatif dengan metode analisis data menggunakan metode padan ekstralingual. Validasi data dilakukan dengan native speaker. Sumber data berupa film berjudul Kizudarake no Akuma. Pengumpulan data penelitian dilakukan dengan cara simak catat. Data diidentifikasi dan dianalisis berdasarkan teori disfemisme dari Allan dan Burridge (2017), teori konteks dari Saifudin (2018) serta teori komponen tutur dari Hymes (2017). Hasil penelitian ini menemukan 7 tipe disfemisme yang muncul dalam sumber data, antara lain : 1) bentuk istilah tabu, 2) makian dan serapah cabul, 3) perbandingan manusia dengan sifat hewan, 4) julukan disfemisme dari karakter fisik, 5) makian dari abnormalitas mental, 6) ejekan tidak hormat dengan nada hinaan, dan 7) istilah dari bahasa asing. Berdasarkan hasil penelitian, dapat disimpulkan bahwa tipe disfemisme yang paling banyak ditemukan adalah tipe 1 dengan jumlah 6 data, terdiri dari 4 data dalam bentuk lisan dengan fungsi : a) menunjukkan kemarahan, b) ungkapan rasa frustasi, dan c) sebagai hinaan atau ejekan; an 2 data dalam bentuk tulisan dengan fungsi : a) sebagai hinaan atau ejekan dan b) ungkapan rasa tidak suka.